Kompetensi Komunikasi Leader Berbasis Indigenous Guna Mendukung Brand Image dan Reputasi Positif IKABOGA - Simamora, Santa Lorita; Pandjaitan, Rosmawaty Hilderiah; Andika , Dicky (Prisani Cendekia, 2024)
Indonesia is known as a country rich in positive ancestral heritage, such as friendliness, politeness, listening, understanding, and respecting others. These positive attitudes play an important role in achieving effective communication, especially in a large organization like IKABOGA, where food experts from all over Indonesia gather. These positive ancestral attitudes need to be applied to support the brand image and positive reputation of IKABOGA that has already been established. The partner in the PKM (Community Partnership Program) for the 2022/2023 period on indigenous-based leader communication competency training to support the brand image and positive reputation of IKABOGA is the IKATAN AHLI BOGA INDONESIA (IKABOGA) organization, located at Jl Penggilingan Baru 1 No.21-27 Rt001 RW 03, Kel. Dukuh, Kec. Kramat Jati, East Jakarta. Established on December 3, 1987, it serves as the sole forum for Indonesian culinary experts. The establishment of IKABOGA was the realization of the idea from the Sub-Consortium of Cooking and Culinary Services under the Directorate of Community Education, Directorate General of Non-Formal Education, Department of National Education, which at that time was chaired by Prof. Dr. W.P. Napitupulu. The elected General Chairperson is Dr. Dewi Motik Pramono, MSi. Currently, the Indonesian Culinary Experts Association has expanded to various regions in Indonesia through the SUBKONSORSIUM pathway. In 2012, DPD IKABOGA was formed in 27 provinces, with 100 DPCs in cities and regencies, totaling approximately 10,000 members (ikabogakb.com. 2023)). The vision of IKABOGA is to build a professional Indonesian culinary society. To achieve its vision, IKABOGA INDONESIA organizes various non-political, independent, and active community activities involving individuals or organizations and collaborates with the government and the business world. The missions of IKABOGA include: a) As a government partner in implementing development in the field of science and technology in culinary and culinary services; b) Conducting training and community course guidance in culinary and culinary services; c) Disseminating information about culinary and culinary services to the public through activities such as seminars, workshops, and others; d) Serving as a channel for member aspirations and activities; e) Fostering the professional development of its members in the field of culinary and culinary services; f) Making the organization an open and responsive forum by facilitating reciprocal communication among IKABOGA Indonesia members, between members and the organization, and between IKABOGA INDONESIA and other organizations and institutions, both governmental and non-governmental (ikabogakb.com. 2023).